The relationship between vitamin D receptor gene polymorphisms and periodontitis in turkish individuals with type 2 diabetes mellitus - DOĞAN, BAŞAK; MEGA TİBER, PINAR (My University, 2022)
© 2022 Wolters Kluwer Medknow Publications. All rights reserved.Background and Aim: Vitamin D receptor (VDR) gene polymorphisms have been implicated in the pathogenesis of many diseases, such as periodontitis and diabetes mellitus (DM). The present study aimed to evaluate the distributions of VDR polymorphisms in diabetic individuals with healthy periodontium (DMH), diabetic individuals with periodontitis (DMP), nondiabetic individuals with healthy periodontium (H), and nondiabetic individuals with periodontitis (P). Material and Methods: A total of 200 individuals (DMH = 40, DMP = 60, H = 40, and P = 60) were recruited. All clinical periodontal parameters, demographical, and biochemical variables were recorded. Blood samples were collected, and genomic DNA was isolated by Purelink® Genomic DNA Mini Kit. Genotyping of VDR polymorphisms ApaI, BsmI, FokI, and TaqI were determined by real-time polymerase chain reaction (PCR) using allele-specific probes. Results: The distribution of the BsmI variant showed differences between DMH and H groups (P = 0.034). In addition, carrying the GG genotype (OR = 0.317; 95% CI = 0.126-0.797; P = 0.013) and the G allele (OR = 2.373; 95% CI = 1.203-4.681; P = 0.012) increased the risk of type 2 DM. Moreover, it was determined that the frequency of CC genotype of FokI variant was higher in DMP compared to DMH (P = 0.046). It was determined that having the CC genotype (OR = 2.706; 95% CI = 1.185-6.176; P = 0.017) and the C allele (OR = 1.917; 95% CI = 0.995-3.694; P = 0.049) increased the risk of periodontitis among diabetic individuals. No differences were detected among groups in the genotype and allele distributions of ApaI and TaqI variants (P > 0.05). Conclusions: The present study showed that the BsmI variant was a risk factor for DM among periodontally healthy individuals and the FokI variant for periodontitis among diabetic individuals.
Keywords: Sağlık Bilimleri; Diş Hekimliği; Klinik Bilimler; Health Sciences; Dentistry; Clinical Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Periodontitis; polymorphism; type 2 diabetes mellitus; vitamin D; GLYCEMIC CONTROL; ASSOCIATION; RISK; DISEASE; VDR; SMOKING; POPULATION; THERAPY; APAI; TAQI